Effects of electrolyte on the removal of fluorine from red mud by electrokinetic remediation - Zhou, Ming (Environmental technology, 2021)
Red mud contains high levels of fluorine compounds. Once these fluorides were released, which led to adverse effects on human health and environment. The aim of this study was to investigate the possible use-electrokinetic remediation (EKR) for the removal of fluorine from red mud and explore the effects of different electrolytes on the remediation process. Three runs of EKR experiments were chosen using distilled water (run A), 0.1 mol/L HCl (run B) and 0.1 mol/L NaOH (run C), respectively. Related parameters for EKR, such as electric current, electro-osmotic flow (EOF) and energy consumption, were analysed. Characterisations of red mud were studied by SEM, XRD and FTIR. Experimental results showed that EKR could effectively remove fluorine pollutants from red mud. Electrolyte can obviously affect fluorine removal in EKR. The removal efficiency of run A, B and C was 57.69%, 66.75%, 60.04%, respectively, and run B (adding 0.1 mol HCl) had the best removal efficiency and the lowest residual fluorine in treated red mud after EKR, because of the highest electric current and EOF in all runs. Energy consumption per kilogram dry red mud of run A, B and C was 0.370, 0.726, and 0.506 kWh/kg, respectively. Experimental results showed that electro-osmosis and electromigration were both important removal mechanisms in EKR of fluorine from red mud. After EKR, the proportion of RESF (the residual fraction of fluorine) increased significantly, now fluorine of treated red mud had a good chemical inertness and had a smaller influence on environment